1982
DOI: 10.3181/00379727-171-41482
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin (Vitamin B12) Analogs Are Absent in Plasma of Fruit Bats Exposed to Nitrous Oxide

Abstract: Fruit bats are an animal model for the neurologic damage which occurs in vitamin B,,-deficient humans. Cobalamin (vitamin BIZ) analogs were not detected in the plasma of fruit bats treated with nitrous oxide (N,O), which inactivates cobalamin. This observation does not lend support to the suggestion that the neurological changes associated with cobalamin inactivation by N,O andor cobalamin deficiency per se may be related to the accumulation of cobalamin analogs. However, although the plasma of control fruit b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Epidemiological studies found an association between neurological diseases or nonspecific deficits (numbness, tingling and muscle weakness) and occupational exposure to N20 among dentists (Cohen et al, 1980;Brodsky et al, 1981). Clinical studies identified neuropathy subsequent to chronic abuse of this anesthetic gas (Layzer et al, 1978), and animal studies demonstrated changes in nerve tissue following experimental exposures (Dinn et al, 1980; Van der Westhuyzen et al, 1982). The fetus is reported to be even more susceptible to N20 than the adult (Vieira et al, 1980;Dyck et al, 1980), such that hyporeactive startle reflexes can be readily demonstrated subsequent to in utero exposures of mice (Rice and Millan, 1985).…”
Section: Introductionmentioning
confidence: 98%
“…Epidemiological studies found an association between neurological diseases or nonspecific deficits (numbness, tingling and muscle weakness) and occupational exposure to N20 among dentists (Cohen et al, 1980;Brodsky et al, 1981). Clinical studies identified neuropathy subsequent to chronic abuse of this anesthetic gas (Layzer et al, 1978), and animal studies demonstrated changes in nerve tissue following experimental exposures (Dinn et al, 1980; Van der Westhuyzen et al, 1982). The fetus is reported to be even more susceptible to N20 than the adult (Vieira et al, 1980;Dyck et al, 1980), such that hyporeactive startle reflexes can be readily demonstrated subsequent to in utero exposures of mice (Rice and Millan, 1985).…”
Section: Introductionmentioning
confidence: 98%
“…However, a few gaseous and volatile compounds can produce transient or permanent neuronal changes that persist after elimination of the agents. Long-term administration of nitrous oxide causes neuronal degeneration in animals and humans, [1][2][3] probably through its capacity to inactivate methionine synthase. 4 Trichloroethylene can cause nerve damage, particularly when given in a rebreathing system.…”
mentioning
confidence: 99%